1997
DOI: 10.1021/jp972194j
|View full text |Cite
|
Sign up to set email alerts
|

Proton NMR Relaxation in Six-Coordinate Low-Spin Iron(III) Tetraphenylporphyrinates:  Temperature Dependence of Proton Relaxation Rates and Interpretation of NOESY Experiments

Abstract: The temperature dependence of longitudinal and transverse relaxation times (T 1 and T 2) has been studied for the pyrrole protons of [(p-Cl)3(p-NEt2)TPPFe(III)(N-MeIm)2]Cl (1), [(p-Cl)(p-NEt2)3TPPFe(III)(N-MeIm)2]Cl (2), and [TMPFe(III)(2-MeImH)2]Cl (3), where TMP = tetramesitylporphyrin and TPP = tetraphenylporphyrin, in the temperature range 190−310 K. All three complexes are paramagnetic and have electron spin S = 1/2. Up to 273 K, all complexes exhibit four distinct pyrrole proton signals, with the asymmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 51 publications
(89 reference statements)
1
36
0
Order By: Relevance
“…(54) In general, if the TjS are less than 10 ms, the likelihood of observing an NOE for protons that are 2.5 Â or more apart for a compound in a non-viscous solvent is very small to negligible. (44) Hence, although we are still convinced that the peak assignments reported earlier are correct, based upon the molecular orbital pictures that had been derived for each of the complexes (54), we cannot prove the assignments by NOESY (or ROESY or ID NOE difference spectroscopy) experiments, because the T,s of the protons involved are just too short to allow buildup of NOEs. Thus, magnitude-NOESY cross peaks can be extremely misleading, and we recommend that magnitude experiments in general, whether NOESY or COSY, not be used, and that spectra never be symmetrized!…”
Section: Expt ( 1 )mentioning
confidence: 71%
See 2 more Smart Citations
“…(54) In general, if the TjS are less than 10 ms, the likelihood of observing an NOE for protons that are 2.5 Â or more apart for a compound in a non-viscous solvent is very small to negligible. (44) Hence, although we are still convinced that the peak assignments reported earlier are correct, based upon the molecular orbital pictures that had been derived for each of the complexes (54), we cannot prove the assignments by NOESY (or ROESY or ID NOE difference spectroscopy) experiments, because the T,s of the protons involved are just too short to allow buildup of NOEs. Thus, magnitude-NOESY cross peaks can be extremely misleading, and we recommend that magnitude experiments in general, whether NOESY or COSY, not be used, and that spectra never be symmetrized!…”
Section: Expt ( 1 )mentioning
confidence: 71%
“…This has happened in our own research program, where apparent NOE cross peaks, between the very resonances that we expected should give NOE cross peaks, were reported as real. (54) We have not been able to detect these cross peaks in phase-sensitive NOESY spectra (44), where full (usually 16-step) phase cycling is used, and we have shown by measurements of the NOE buildup curve for a related complex and by calculations (44) that the protons which gave the apparent NOE cross peaks in the earlier study are too far apart (>5A) to give a measureable NOE cross peak with the solvent viscosity used in that study (CD 2 C1 2 at -40 to -50 °C). (54) In general, if the TjS are less than 10 ms, the likelihood of observing an NOE for protons that are 2.5 Â or more apart for a compound in a non-viscous solvent is very small to negligible.…”
Section: Expt ( 1 )mentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we have undertaken an NMR measurement of the rate of axial ligand rotation and rotational Δ H ⧧ , Δ S ⧧ , using the T 2 's of the pyrrole protons. It has been found that the temperature dependence of transverse relaxation rates of pyrrole protons in [(TMP)Fe(2-MeImH) 2 ] + is bimodal in that the T 2 's increase with temperature at low temperatures and decrease at high temperatures preceding the collapse of the four-peak pyrrole proton pattern. This behavior is compatible with the hypothesis that at low temperatures the T 2 's of the pyrrole protons are the intrinsic T 2 's, which increase with temperature, whereas at the high temperatures the T 2 values are significantly shortened by exchange …”
Section: Introductionmentioning
confidence: 99%
“…In this study, we will use simulation of the experimentally observed pyrrole proton T 2 's in [(TMP)Fe(2-MeImH) 2 ] + to demonstrate that the presence of cyclic chemical exchange quantitatively explains their bimodal behavior . The rate of rotation of axial ligands can be measured from the temperature dependence of the T 2 's as the rate constant of chemical exchange induced by such rotation.…”
Section: Introductionmentioning
confidence: 99%